Role of Osmolytes in Regulating Immune System - Kumar, Tarun; Yadav, Manisha; Rajendrakumar Singh, Laishram (Current Pharmaceutical Design, 2016)
Background: The immune system has evolved to protect the host organism from diverse range of pathogenic microbes that are themselves constantly evolving. It is a complex network of cells, humoral factors, chemokines and cytokines. Dysregulation of immune system results in various kinds of immunological disorders. There are several external agents which govern the regulation of immune system. Recent studies have indicated the role of osmolytes in regulation of various immunological processes such as Ag-Ab interaction, Ig assembly, Ag presentation etc. Scope of Review: In this present review, we have systematically discussed the role of osmolytes involved in regulation of several key immunological processes. Major Conclusion: Osmolytes are involved in the regulation of several key immunological processes such as immunoglobulin assembly and folding, immune cells proliferation, regulation of immune cells function, Ag-Ab interaction, antigen presentation, inflammatory response and protection against photo-immunosuppression. Hence, osmolytes and their transporters might be used as potential drug and drug targets respectively. General Significance: This review is therefore designed to help clinicians in development of osmolyte based therapeutic strategies in the treatment of various immunological disorders. Appropriate future perspectives have also been included.
Keywords: aggregation